Statistical analysis of photodegradation of methylene blue dye under natural sunlight - Muthukumar, Chandhini; Alam, Saad; Iype, Eldhose; B.G., Prakash Kumar (Optical materials, 2021)
In this study, photocatalysis experiments were conducted under natural sunlight irradiation to degrade methylene blue (MB) dye in the presence of rGO/TiO2. The individual effect of three control factors, namely MB dye concentration, photocatalyst (PC) loading and pH were studied. In addition, these factors were optimized by the Taguchi method. The results reveal that the most influential factor was pH followed by MB dye concentration and PC loading. The optimal conditions for dye removal were at MB concentration of 80 ppm with a PC loading of 0.15 g at 8 pH. It showed 95% degradation. Moreover, regression analysis was performed to validate the experimental results with the predicted results. This is followed by characterization of the PC by TGA, FTIR, FE-SEM, XPS, XRD, UV–Vis DRS, GC-MS, PL and ESR to determine the stability, concentration, bandgap, and to validate the anchoring of TiO2 on rGO. [Display omitted] •The photodegradation of methylene blue dye was studied under natural sunlight.•Taguchi method and ANOVA was used to optimize and analyse the influential process parameters.•The photodegradation of a colourless organic compound like phenol was studied.•The lowest amount of H2O2 was used to enhance photodegradation.